The Effect of Price on Service Quality, Customer Satisfaction and Customer Loyalty: Case Study on One of The E-Commerce - Bulan Tati Fitria; Haris Nurdiansyah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
Sales are a crucial indicator of a company's ability to carry out its operations successfully. Sales in this context refer to products or services that the business has offered and that customers have accepted or used favorably. A firm's level of sales indicates how successful it is in conducting business operations; the higher the sales level a company achieves, the more successful the company is. The impact of price on customer satisfaction and service quality is investigated in this study. Researchers employed partial least squares (PLS), a non-parametric method, to test the research model. The research model was also predicted using a cross-sectional survey with 100 respondents using one e-commerce site. The findings demonstrated that price impacted customer loyalty, satisfaction, and service quality. The findings also demonstrate the critical role that strategic price policies play in boosting consumer loyalty and happiness.